Numerical investigations of ship forces during lockage - Thorenz, Carsten; Schulze, Lydia (Journal of Coastal and Hydraulic Structures, 2021)
The evaluation of ship forces for planned or existing navigation lock systems is essential for a sound design in terms of safety, cost and speed. It is a complex task that requires knowledge in physical understanding and modelling of the ongoing hydraulic processes during the lock filling. In this case study, focus is put on the ability to analyse the magnitude of the ship forces with a three-dimensional computational fluid dynamics (CFD) model based on the OpenFOAM software package. The inhouse state-of-the-art of the ship force evaluation during levelling with the means of three-dimensional numerical modelling is presented. The results are compared to physical model tests in scale 1:25 and discussed. The outcome showed a very good agreement in terms of flow rates and longitudinal ship forces. The results for the transversal ship forces are promising because the system behaviour is reproduced but the accuracy of the peak values is still to be enhanced. An analysis shows several possible sources for these discrepancies.